1) sistem:
x = y + 2
2x + 3y - 4 = 0
rezultă : (înlocuim în a 2-a expresie x cu y +2)
x = y + 2
2(y + 2) + 3y - 4 = 0
rezultă:
x = y + 2
2y + 4 + 3y - 4 = 0
rezultă:
x = y + 2
5y = 0
rezultă:
x = 2
y = 0
2)sistem:
y = 2
2x + 3y - 9 = 0
rezultă:
y = 2
2x + 6 - 9 = 0
rezultă:
y = 2
2x - 3 = 0
rezultă:
y = 2
2x = 3
rezultă
y = 2
x = 3/2 = 1,5
3) sistem:
2x = 3y
x + 6y = 5
rezultă:
2x = 3y
x = 5 - 6y
rezultă:
2(5 - 6y) = 3y
x = 5 - 6y
rezultă:
10 - 12y = 3y
x = 5 - 6y
rezultă:
-12y - 3y = -10
x = 5 - 6y
rezultă:
-15y = -10
x = 5 - 6y
rezultă:
y = 10/15 = 2/3
x = 5 - 12/3
rezultă:
y = 2/3
x = (15 - 12)/3
rezultă:
y = 2/3
x = -1
4) sistem:
x - 2y = 3
y = x + 1
rezultă:
x - 2(x + 1) = 3
y = x + 1
rezultă:
x - 2x - 2 = 3
y = x + 1
rezultă:
-x = 5
y = x + 1
rezultă:
x = -5
y = -4
sper că te-am ajutat, succese))